Pemakanan dan implikasinya terhadap pembangunan insan: satu analisis berdasarkan Kitab Fi Zilal Al-Quran / Halipah Hamzah and Hanani Ahmad Zubi - Hamzah, Halipah; Ahmad Zubir, Hanani (Univeristi Teknologi MARA, Sabah, 2019)
One of the main elements of human life needs is nutrition. Nutrition plays an important role in human development, be it physical, spiritual, mental or emotional development. The concept of food in Islam is classified into halal food, makruh food, illegal food and doubtful food. The practice of halal nutrition is strongly emphasized by Islam aimed at ensuring that the physical and spiritual needs of Muslims are always harmonious, holy and loved by Allah SWT. Contrary to many illegal eating practices, it is harmful to their diet. Among them, the food will affect the soul of the eater so that he prefers evil and hates obedience, poses a danger and affects both the physical and the mental. In addition, eating habits beyond the limit also cause a variety of diseases to the diet. This is reflected in the Quran and the Hadith. The Book of Zilal al-Quran is one of the many interpretive books in the market that helps Muslims to understand and interpret the verses of the Quranic scriptures clearly and perfectly.